An Analytical Method for Assessing Optimal Storage Conditions of Gingival Crevicular Fluid and Disclosing a Peptide Biomarker Signature of Gingivitis by MALDI‐TOF MS. Issue 5 (23rd April 2018) - Preianò, Mariaimmacolata; Maggisano, Giuseppina; Murfuni, Maria Stella; Villella, Chiara; Pelaia, Corrado; Montalcini, Tiziana; Lombardo, Nicola; Pelaia, Girolamo; Savino, Rocco; Terracciano, Rosa
Abstract : Purpose: Gingival crevicular fluid (GCF) is an important diagnostic source of biomarkers for both periodontitis and gingivitis. However, GCF peptide signature may change depending on factors such as handling and storage. Here we propose a standardized methodology for GCF analysis by MALDI‐TOF/TOF‐MS in order to distinguish a characteristic peptide signature of gingivitis. Experimental design: The best storage/handling conditions which may ensure the stability of the endogenous peptidome in GCF is determined and then MALDI‐TOF MS comparative analysis is performed. Reproducible GCF MALDI‐TOF signatures between two groups of gingivitis ( n  = 10) and healthy ( n  = 10) subjects are compared. Results: A pattern of five peptides resulted differentially expressed between gingivitis and healthy groups. Interestingly, among these biomarkers the C‐terminal fragment of alpha‐1‐antitrypsin (AAT) namely C‐36 peptide and two different PTMs of the full‐length S100A9 protein are found. Conclusions and clinical relevance: The method described provides a rapid comparative analysis of GCF signatures between periodontally healthy and gingivitis subjects. A pattern based on the expression of endogenous peptides and their PTMs is identified in GCF as putative biomarkers of gingivitis. These findings improve the knowledge of the inflammatory, immune, and structural substrates which might have a key role in the pathogenesis of gingivitis.